Influence of very long aging on the relaxation behavior of flame‐retardant printed circuit board epoxy composites under mechatronic conditions. Issue 2 (4th April 2013) - Lé‐Magda, Mélanie; Dargent, Eric; Puente, Jorge Arturo Soto; Guillet, Alain; Font, Emmanuelle; Saiter, Jean‐Marc
<x xml:space="preserve">Abstract</x> Very long aging times, up to 15, 100 h (629 days) at 110°C, were achieved on flame‐retardant printed circuit board laminates commonly used in automotive design. This composite was fabricated from glass fibers embedded in an epoxy resin. Aging was performed in an oven under an air atmosphere at a temperature lower than the glass‐transition temperature. Temperature‐modulated differential scanning calorimetric analysis was used to investigate the influence of such aging on the glass‐transition phenomena. A new amorphous phase appeared during aging. By extending the analysis to samples collected at different thicknesses, we demonstrated the existence of a time‐dependent gradient of the properties. A skin–core structure was evidenced, and this slowed down oxidation and allowed physical aging to occur in the bulk sample. An exponential law described the variations of the glass‐transition of the new external compound. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 786‐792, 2013